PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA LEMBAGA “BUMI DAMAI“ DESA KUWIRAN KECAMATAN KARE KABUPATEN MADIUN - Ninik Srijani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
The purpose of this study was to influence of leadership style on employee performance in institution Bumi Damai Madiun. The sample in this study all existing employees in the institution Bumi Damai Madiun, totaling 34 people. Data collection using questionnaires. In analyzing the data used statistical methods to test the product moment correlation is valid whether or not the instruments used and the method of regression tests for testing the hypothesis put forward in this study. The results showed that leadership style has relationships and a positive influence on the performance of employees at the Institute Bumi Damai Madiun. It is obtained from the correlation test that shows the value of rhitung is rtabel 0.339 0.740 whereas, on the other hand is 0.000 while the magnitude Sighit Sigprob 0.05. This means that the value rhitung ≥ rtabel (0.740 ≥ 0.339) or ≤ Sighit Sigprob (0.000 ≤ 0.05) meaning a rejection of H0 to show that leadership style has a relationship with employee performance on Institute Bumi Damai Madiun.  Further test results were also obtained Fisher, Fhitung value is 38.843 while the F table at 4.149, on the other hand is 0.000 while the magnitude Sighit Sigprob 0.05. This means that the value Fcount Ftabel ≥ (≥ 38.843 4.149) or ≤ Sighit Sigprob (0.000 ≤ 0.05) meaning a rejection of H0 which indicates that there is the influence of leadership style on the performance of employees at the Institute Bumi Damai Madiun. Besides t test results obtained, is 6.232 whereas tcount ttabel of 2.037, on the other hand is 0.000 while the value Sighit Sigprob 0.05. This means that tcount ≥ TTable (6.232 ≥ 1.694) or ≤ Sighit Sigprob (0.000 ≤ 0.05) meaning a rejection of H0 which shows that there are different leadership style influence on the performance of employees at the Institute Bumi Damai Madiun. R 2 of 0.548 results showed that 54.8% of employees affected by the performance variable leadership style, while the remaining 45.2% is influenced by other factors.